Composition and diversity pattern of plant community with elevational gradient in Yuanjiang dry-hot valley - LI Zhenxue1, DAO Zhigang1, ZHAO Gaojuan2,3*, CHEN Chao4, ZHANG Shubin2,3, ZHANG Chunzao1, LI Shouqi1, WEN Handong4, LI Tianliang4, CHEN Yajun2,3,4 (Guangxi Zhiwu)
Although dry-hot valleys in Southwest China have shaped a landscape with a vegetation appearance similar to that of African savannas, they are different from the African savannas because of the vertical geomorphology and climate type formed by the depth of river valley and the blocking of air flow by mountains in this region, which are more prone to land degradation, species loss and plant community heterogeneity. However, previous studies have paid little attention to the vertical distribution pattern and main regulatory factors of plant community species composition and diversity. In this study, the soil nutrients, meteorological factors and species composition of 450 m(low elevation, LE), 850 m(middle elevation, ME), 1 250 m(middle-high elevation, M-HE)and 1 650 m(high elevation, HE)were investigated in Yuanjiang National Nature Reserve(Yuanjiang dry-hot valley ), and the species important values, α-diversity and β-diversity were calculated to explore their changes with the elevation gradients. The results were as follows:(1)Soil organic carbon(SOC)and nitrous nitrogen(NO3--N)at LE were significantly higher than those at other elevations.(2)The species composition and species importance value of different elevations were significantly different.(3)The species diversity of HE was high, while the species abundance of LE was high. In α-diversity, Shannon-Wiener diversity index and Pielou evenness index increased with elevation, while Simpson dominance index of tree species reached its maximum at LE. In β-diversity Jaccard and Sorenson similarity indexes of communities in adjacent elevations increased with the elevations, but those of communities in non-adjacent elevations decreased with the elevations to compare with adjacent elevations.(4)CCA showed that SWC, SOM, NO3--N and NH4+-N were the main factors affecting species differences at different elevations. It is concluded that the diversity, similarity and stability of plant communities in the hot-dry valley increased with the increasing of elevation, and the future research on the restoration of plant communities and their response and adaptation to drought should consider the spatial heterogeneity of the community, and different protection and restoration measures also should be formulated accordingly in this region.